A prospective multicentre randomized placebo‐controlled superiority trial in patients with suspected bacterial endophthalmitis after cataract surgery on the adjuvant use of intravitreal dexamethasone to intravitreal antibiotics. Issue 4 (7th December 2017) - Manning, Sonia; Ugahary, Luana C.; Lindstedt, Eric W.; Wubbels, René J.; van Dissel, Jaap T.; Jansen, Jan T.G.; Gan, Ivan; van Goor, Arnoud T.; Bennebroek, Carlien A.; van der Werf, Dymph J.; Ossewaarde‐van Norel, Annette; Mayland Nielsen, Chris C.; et al.
Abstract: Purpose: We aimed to determine whether intravitreal dexamethasone as an adjuvant to intravitreal antibiotics is beneficial in the treatment of suspected bacterial endophthalmitis after cataract surgery. Methods: Randomized, placebo‐controlled superiority trial in three tertiary referral centres in the Netherlands. Patients with suspected bacterial endophthalmitis within 6 weeks after cataract surgery were eligible. A diagnostic vitreous biopsy was taken for culture, and patients received intravitreal injections of 400  μ g dexamethasone (without preservatives) or placebo, in addition to 0.2 mg vancomycin and 0.05 mg gentamicin. The vancomycin and dexamethasone or placebo injections were repeated once at day 3 or 4. Primary outcome measure was best‐corrected visual acuity (BCVA) at 1 year. Results: Between 1 November 2004 and 1 March 2014 (excluding two interruptions totalling 20 months), 324 eligible patients presented. A total of 167 patients (81 dexamethasone, 86 placebo) were available for the intention‐to‐treat analysis. Biopsies of 114 patients (68%) were culture‐positive. Final BCVA did not differ between the dexamethasone and the placebo group (logMAR 0.31 ± 0.58 versus 0.27 ± 0.50; p = 0.90), nor did the number of patients with final vision of no light perception (LP, 7 versus 13). Pain, corneal oedema, the absence of a red fundus reflex on presentation, LP on presentation and culture of virulent pathogens from biopsy were statistically significantly associated with an unfavourable visual outcome. Conclusion: Intravitreal dexamethasone without preservatives as an adjuvant to intravitreal antibiotics does not improve visual acuity (VA) in patients treated for suspected bacterial endophthalmitis after cataract surgery.